WORK-LIFE BALANCE TO DECREASE WORK-FAMILY CONFLICT DURING THE COVID-19 PANDEMIC - Ali Amran; Meiliani Luckieta; Doni Purnama Alamsyah; Adi Suparwo (Faculty of Economics and Business, University of Pasundan, 2022)
This study aims to review the support of work-life balance and work-from-home to work-family conflict. The research method was conducted through a survey of 110 employees from several cities in Indonesia. The Data obtained through the questionnaire was analyzed with the Structural Equation Modeling approach. The analysis tool used in this research is Lisrel. The research results found that work-from-home has an effect on work-life balance, and work-life balance can decrease work-family conflict. Furthermore, work-from-home is not able to directly decrease work-family conflict. The research found that work-family conflict can be indirectly controlled by work-fromhome through the mediation of work-life balance. The importance of work-life balance in mediating work-from-home and work-family conflict raises a mediation model that is a mediation model of work-life balance to decrease work-family conflict. This information is useful for companies in evaluating work-family conflict through the implementation of work-from-home.